2019
DOI: 10.21608/aprh.2019.14237.1087
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tacrolimus in Egyptian Liver Transplant Recipients: Role of the Classic Co-variables

Abstract: Objectives: This work was performed to study the pharmacokinetics of tacrolimus in adult liver transplant recipients after optimization of all the known classic factors contributing to inter-patient variability in whole blood tacrolimus levels. Also, to detect if any variability in whole blood tacrolimus levels still exists or this variability is only a function of the classic co-variables so that their optimization will diminish or eliminate it. Methods: Twenty-Six male patients with end-stage liver disease u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…If the top-down approach was attempted without information from the bottom-up approach, the model would not have been identifiable to the level of unbound metabolic CL int, and the effect would have been masked by the high level of uncertainty and interpatient variability, as reported by other top-down-only studies. 4 , 43 Adopting this approach enables the incorporation of available or known covariate effects as strong fixed priors based on clinical and biochemical data. Subsequently, other undefined covariate effects of interest on the pharmacokinetic parameters were investigated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If the top-down approach was attempted without information from the bottom-up approach, the model would not have been identifiable to the level of unbound metabolic CL int, and the effect would have been masked by the high level of uncertainty and interpatient variability, as reported by other top-down-only studies. 4 , 43 Adopting this approach enables the incorporation of available or known covariate effects as strong fixed priors based on clinical and biochemical data. Subsequently, other undefined covariate effects of interest on the pharmacokinetic parameters were investigated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) is essential for achieving therapeutic trough concentrations. Despite the fact that monitoring blood trough concentrations is an effective method for adjusting tacrolimus oral doses, clinical studies have reported that it may not be valuable for future dosage estimation and may also not be an accurate assessment of overall drug exposure among various individuals [ 17 , 23 , 24 , 25 , 26 ]. It is sometimes challenging to achieve and maintain target tacrolimus trough concentrations despite periodic tacrolimus TDM [ 3 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
“…The narrow therapeutic index of tacrolimus necessitates the frequent monitoring of the whole-blood concentration to achieve optimal therapeutic levels while drug toxicity [ 17 , 23 , 24 , 25 , 26 ]. Even a small variance in the dose or concentration can lead to therapeutic failure.…”
Section: Introductionmentioning
confidence: 99%
“…It presents a narrow therapeutic window, requiring strict monitoring and constant dosing modification [ 5 ]. Differences in tacrolimus absorption [ 6 , 7 ], metabolism [ 8 , 9 ], and drug interactions [ 6 , 10 , 11 ] often lead to either sub- or supratherapeutic trough levels [ 12 , 13 ]. Above-target trough levels are associated with adverse effects, whereas those below target are associated with an increased risk of rejection and development of de novo donor-specific antibody (dnDSA) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the pharmacokinetics and pharmacodynamics of tacrolimus [6,[8][9][10][11], several formulas have been developed to explore the correlation of tacrolimus trough levels with graft outcomes. Intrapatient variability (IPV) calculates the variability coefficient by dividing the standard deviation of tacrolimus samples by their mean [16,17].…”
Section: Introductionmentioning
confidence: 99%